Color Science and Photometry for Lighting with LEDs and Semiconductor Nanocrystals - Erdem, Talha; Demir, Hilmi Volkan; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book reviews the application of semiconductor nanocrystals also known as colloidal quantum dots (QDs) to LED lighting for indoors and outdoors as well as LED backlighting in displays, summarizing the color science of QDs for lighting and displays and presenting recent developments in QD-integrated LEDs and display research. By employing QDs in color-conversion LEDs, it is possible to simultaneously accomplish successful color rendition of the illuminated objects and a good spectral overlap between the emission spectrum of the light source and the sensitivity of the human eye at a warm white color temperature - something that is fundamentally challenging to achieve with conventional sources, such as incandescent and fluorescent lamps, and phosphor-based LEDs.
1.Introduction -- 2.Light Stimulus and Human Eye -- 3.Colorimetry for Led Lighting -- 4.Metrics for Light Source Design -- 5.Common White Light Sources -- 6.How to Design Quality Light Sources with Discrete Color Components -- 7.Future Outlook.
Keywords: Telecommunication; Lasers; Nanotechnology; Signal processing; Microwaves, RF Engineering and Optical Communications; Laser; Nanotechnology; Signal, Speech and Image Processing